Las rupturas del 68 en el cine de América Latina - Sala, Jorge (Imagofagia, 2021)
Sobre Mestman, Mariano (Coord.) Las rupturas del 68 en el cine de América Latina, Buenos Aires, Akal: 2016, 480 pp., ISBN: 978-987-4544-6-9.